Ethics of Artificial Intelligence - Lara, Francisco; Deckers, Jan. (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This book presents the reader with a comprehensive and structured understanding of the ethics of Artificial Intelligence (AI). It describes the main ethical questions that arise from the use of AI in different areas, as well as the contribution of various academic disciplines such as legal policy, environmental sciences, and philosophy of technology to the study of AI. AI has become ubiquitous and is significantly changing our lives, in many cases, for the better, but it comes with ethical challenges. These challenges include issues with the possibility and consequences of autonomous AI systems, privacy and data protection, the development of a surveillance society, problems with the design of these technologies and inequalities in access to AI technologies. This book offers specialists an instrument to develop a rigorous understanding of the main debates in emerging ethical questions around AI. The book will be of great relevance to experts in applied and technology ethics and to students pursuing degrees in applied ethics and, more specifically, in AI ethics. .
Chapter 1: Introduction -- Part I: Can an AI System Be Ethical? -- Chapter 2: Bias and Discrimination in Machine Decision-Making Systems -- Chapter 3: Opacity, machine learning and explainable AI -- Chapter 4: The Moral Status of AI Entities -- Part II: Ethical Controversies About AI Applications -- Chapter 5: Ethics of Virtual Assistants -- Chapter 6: Ethics of Virtual Reality -- Chapter 7: Ethical Problems of the Use of Deepfakes in the Arts and Culture -- Chapter 8: Exploring the Ethics of Interaction with Care Robots -- Chapter 9: Ethics of Autonomous Weapons Systems -- Part III: The Need for AI Boundaries -- Chapter 10: Ethical Principles and Governance for AI -- Chapter 11: AI, Sustainability, and Environmental Ethics -- Chapter 12: The Singularity, Superintelligent Machines, and Mind Uploading: The Technological Future?
Keywords: Technology -- Moral and ethical aspects; Information technology -- Moral and ethical aspects; Artificial intelligence; Ethics of Technology; Information Ethics; Artificial Intelligence